An aged-related structural study of DHPR tetrads in peripheral couplings of human skeletal muscle - Laura Pietrangelo; Rosa Mancinelli; Stefania Fulle; Simona Boncompagni (PAGEPress Publications, 2024)
Among the numerous changes that occur in skeletal muscle during aging, the reduced regeneration potential after an injury is largely due to the impaired ability of satellite cells to proliferate and differentiate. Herein, using the freeze-fracture electron microscopy technique, we analyzed both the incidence and size of dihydropyridine receptors (DHPRs) tetrads (4 particles) in cultured myotubes from a young subject (28 years) after 9 days of differentiation and from an old subject (71 years) after 9 and 12 days of differentiation. Compared to young myotubes, at 9 days of differentiation old myotubes exhibited: i) a lower incidence and a smaller size of DHPR clusters and ii) a lower number of complete tetrads. At 12 days of differentiation values of incidence, size and number of complete tetrads in old myotubes were instead comparable with those of young myotubes at 9 days of differentiation. Collectively, these results indicate that in aged myotubes the synthesis process of the proteins involved in the excitation-contraction coupling mechanism, such as the DHPR, is somehow slowed, supporting previous studies evidence of a decrease in the differentiation potential of myotubes from elderly individuals.